COMMUNITY-BASED ORGANIC WASTE PROCESSING USING BSF MAGGOT BIOCONVERSION - Mohamad Satori; Ivan Chofyan; Yuliadi Yuliadi; Otong Rukmana; Ira Ayu Wulandari; Fathiya Izzatunnisaa; Rifky Pajar Kemaludin; Aji Saeful Rohman (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
Organic waste is the largest composition of waste generated by the people of Indonesia, which is around 50-60%. This type of waste, especially food waste, is easy to smell if it is stored for too long so that it has the potential to pollute the environment. On the other hand, organic waste has good nutrients that can be generated, including through BSF (Black Soldier Fly) maggot bioconversion treatment. The BSF maggot bioconversion method is a method of processing organic waste which is carried out by converting organic matter into other products that are useful and have added value by utilizing biological processes from microorganisms and enzymes. Organic waste treatment with this method is generally carried out on a community-based basis and is integrated with the development of agriculture, fisheries and animal husbandry, because maggot cultivation produces commodities of economic value such as compost and maggot larvae. Compost contains very good nutrients so that it can be used for organic farming and maggot contains high protein that can be used for animal feed and fisheries. The implementation of this program was piloted in the boarding school community, namely the Az-Zakaria Islamic Boarding School which is managed by the Az-Zakaria Islamic Education Foundation (YPI) in Sindangbarang Village, Jalaksana District, Kuningan Regency. The result of this implementation is the formation of a new group of entrepreneurs engaged in the cultivation and utilization of BSF maggots.